Approaches to disruptive change: The contribution of complexity science to futures studies. (December 2020) - Bredikhin, Sergey
Highlights: Conceptual ambiguity of the weak signal concept hinders wider usage of insights from complexity science in futures studies. The notion of Dragon-Kings helps to link the idea of weak signals with a cognate topic of early warnings signals. Early warning signals concept could enhance weak signal analysis with both new techniques and theoretical basis. A new generic definition of weak signal can be formulated based on the 'systemic' view of its nature. Abstract: We set out to establish the place of Weak Signals at the conceptual intersection between the fields of futures and complexity studies as a qualitative counterpart to the so-called Early Warning Signals (of regime shift). After briefly presenting the scope of the Weak Signal concept and associated problems with positioning such a controversial construct against the complexity field, we investigate how theoretical and practical implications of studying qualitative changes in a complex system's state allow for particular classes of phenomena to announce impactful events in advance. Finally, we reflect on the prospective ways of augmenting the Weak Signals concept by fusing it with the notion of Early Warning Signals and the consequent opportunities provided by bridging the fields of complexity and futures studies.